Prediksi Laju Perambatan Retak Melar pada Baja Austenitik 316L Menggunakan Data Uji Melar dan Metode NSW - Ekaputra, I Made Wicaksana (Jurnal Rekayasa Mesin, 2019)
In this study, an experimental creep crack growth rate (CCGR) of austenitic steel AISI 316L was predicted from the creep constant values and Nibkin Smith Webster (NSW) method. The experimental CCGR data were obtained from the CCG test under four different load conditions ranging from 6000 to 7000 N at 525 oC. The creep constants, A and n were obtained from the uniaxial creep rupture test under various load conditions, ranging from 180 to 225 Mpa at 525 oC. The creep constants were determined both from the minimum and average creep strain rate data. By applying the creep constants and NSW method, the predicted CCGR curve was generated and compared with the experimental CCGR curve. The result showed that the predicted CCGR curve based on the minimum creep strain rate data was found to be close to the experimental CCGR curve. The significant portion of creep crack growth’s lifetime of austenitic steel AISI 316L was occupied by the crack propagation (steady stage) period rather than crack initiation and/or fracture periods. In addition, plane stress and strain conditions could also be determined from the predicted CCGR curve. It was observed that the experimental CCGR curve was located near the plane strain condition where no deformation occurred in the lateral direction.